2022
DOI: 10.1111/pde.15193
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous lesions and mitochondrial hearing loss: A case report

Abstract: Pathogenic sequence changes in mitochondrial DNA (mtDNA) are one of the most common causes of genetic hearing loss. We report an infant with palmoplantar hyperkeratosis, extrapalmoplantar cutaneous features and mitochondrial sensorineural hearing loss caused by the previously reported pathogenic NC_012920: m.7445A > G sequence change in the mitochondrial gene COX1 (COX1, MT-CO1).Next generation sequencing-based technology was key for the diagnosis and management of this patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Family #F3. A previously reported homplasmic pathogenic sequence change in the mitochondrial mitCOX1 (also known as MT-CO1 gene; NC_012920: m.7445A>G ( Martin et al, 2000 ) was identified in a 1-year-old infant with sensorineural hearing loss, palmoplantar keratosis and other extra palmoplantar cutaneous features further described in an already published case report ( Moreno-Artero et al, 2022 ) (#P47 in Table 2 ). Her mother also presented with severe-to-profound bilateral hearing loss since childhood, and she got cochlear implants in both ears.…”
Section: Resultsmentioning
confidence: 79%
“…Family #F3. A previously reported homplasmic pathogenic sequence change in the mitochondrial mitCOX1 (also known as MT-CO1 gene; NC_012920: m.7445A>G ( Martin et al, 2000 ) was identified in a 1-year-old infant with sensorineural hearing loss, palmoplantar keratosis and other extra palmoplantar cutaneous features further described in an already published case report ( Moreno-Artero et al, 2022 ) (#P47 in Table 2 ). Her mother also presented with severe-to-profound bilateral hearing loss since childhood, and she got cochlear implants in both ears.…”
Section: Resultsmentioning
confidence: 79%
“…There is no mention of whether the patient received antioxidants, vitamins or co‐factors (mitochondrial cocktail) in addition to oral nystatin, topical miconazole, topical corticosteroids and topical application of emollients and pimecrolimus 1 . Since MiDs occasionally respond positively to mitochondrial cocktails, 2 such a therapy could show an additional beneficial effect.…”
mentioning
confidence: 99%
“…
I read with interest the article by Moreno-Artero et al on a 13-monthold female with a mitochondrial disorder (MiD), phenotypically manifesting with hypoacusis, palmoplantar keratoderma (PPK), scaly plaques, and perioral erythema due to the mtDNA variant m.7445A > G in MT-CO1. 1 The authors concluded that diagnosis, management, and counseling of patients with impaired hearing is facilitated by genetic workup with next generation sequencing (NGS). The study is excellent but has limitations that raise concerns and should be discussed.
…”
mentioning
confidence: 99%
See 1 more Smart Citation